Pencapaian perancangan strategik UCS 2022 - Awal, Asmah; Abdul Rahman, Ahmad Taufek; Isa, Badrul; Ghazali, Rosmadi; Bakar, Alfina; Alang Idris, Noor Alzura; Muslim, Junaidi; Mohd Jais, Mohamad Hamidi; Husin, Zamani Umar; Rajan, Shantakumari; Abdul Kader Jailani, Sri Fatiany; Omar, Mazlifah; et al. (Unit Komunikasi Korporat, UiTM Cawangan Selangor, 2023)
Laporan pencapaian perancangan strategik UiTM Cawangan Selangor bagi tahun 2022